Pengaruh Kegiatan Discharge Dry Bulk Cargo terhadap Short Cargo di PT Terminal Teluk Lamong - Teuku Ali Wabiansyah; Elly Kusumawati; Anak Agung Istri Sri Wahyuni; Rizqi Aini Rakhman (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
The Influence of Dry Bulk Cargo Discharge Activities on the Occurrence of Short Cargo at PT. Terminal Trluk Lamong Dry bulk unloading activities using grab ship unloaders (GSU) and conveyors often result in an unloading process that differs from the specified loading plan, resulting in a quantity of dry bulk cargo that is lower than stated in the document, known as short cargo.This research uses an associative quantitative method to determine the relationship between loading duration (X1), cargo volume (X2), and short cargo (Y), as well as the simultaneous influence of each factor on short cargo. Multiple linear regression data analysis techniques are used to test the hypothesis, and the data are processed using the SPSS version 27 program. The results showed that unloading duration and cargo volume have a significant, though partial, effect on short cargo. They have an influence of 176.5% and 0.6%, respectively. The variables of loading duration and cargo volume cause short cargo to occur simultaneously. Thus, each factor has an 85.2% simultaneous influence on short cargo, while the remaining 14.8% is influenced by factors outside the scope of the study.